CD1c(+) myeloid dendritic cells in myeloid neoplasia. Issue 4 (22nd December 2015) - Meyerson, Howard J.; Osei, Ebenezer; Schweitzer, Karen; Blidaru, Georgetta; Edinger, Alison; Schlegelmilch, June; Awadallah, Amad; Goyal, Tanu
Abstract : We determined the normal level and phenotype of CD1c(+) myeloid dendritic cells (MDCs) in blood and bone marrow and evaluated the level of CD1c(+) MDCs in 295 myeloid neoplasms. CD1c(+) MDCs were increased above the mean level of non‐neoplastic hospital controls in 18.0% (53/295) of myeloid malignancies, increased three standard deviations above the control mean in 14.2% (42/295) with a 10‐fold or more increase compared to mean in 6.8% (20/295). Increased CD1c(+) MDCs were associated with chronic myelomonocytic leukemia (CMML) (12/24, 50%) and acute myeloid leukemia (AML) (31/140, 22%) with a strong association with AML with the inv(16) cytogenetic abnormality. The cells were not increased in chronic myelogenous leukemia (CML) and rarely increased in non‐CML myeloproliferative neoplasms (MPN) and myelodysplastic syndromes (MDS). Immunohistochemical staining of cases with increased CD1c(+) MDCs did not reveal clustering of the cells unlike that observed with myeloid neoplasms associated with increased plasmacytoid dendritic cells. Our findings indicate CD1c(+) MDC elevations are not uncommon in myeloid leukemias and are associated with CMML and AML, particularly AML with inv(16). © 2015 International Clinical Cytometry Society